Light control at the micro scale. (Research'eu results magazine)
The possibility of overcoming the limits of focusing and collimating laser beams and achieving sub-wavelength resolution has been the focus for imaging applications. It has led scientists to develop digital light switches and engineer materials' electromagnetic properties for this very purpose.